Pengaruh Teknologi Informasi Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Informasi Keuangan : Studi Kasus Masyarakat Pengguna myIM3 - Afra, Zahrina Sazida; Kurnianingsih, Heny Triastuti; Damanik, Cindy Tasya; Sinaga, Alnayca (JFAS : Journal of Finance and Accounting Studies, 2025)
The purpose of this study is to find out and analyze the partial and simultaneous influence of the use of information technology and human resource competence on the quality of financial reporting information in the Work Unit of the Community and Village Empowerment Office of Tapin Regency. The population and sample of this study are all people in the city of Medan, so a sample of approximately 60 people was obtained. The data analysis technique uses multiple linear regression methods, F-test and T-test